Analisis Pengaruh Minat Beli Produk Skincare di E-Commerce - Sinambela, Fitriana Aidnilla; Putri, Amelia (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to find out, explain, identify and analyze the influence of factors that influence buying interest in skincare products in e-commerce. The independent variables used in the object of this research include the variables perceived quality, perceived risk, perceived benefits, perceived endorsement, subjective norms. The intervening variable used is attitude and the dependent variable used is purchase intention. This research applies quantitative research methods in data collection and the technique used by the research is purposive sampling technique, the sample used reached 279 respondents using skincare in Batam city. The research analysis method uses smart PLS. This research produces various results, namely that there is a significant positive relationship between the perceived benefits variable and the Attitude variable. There is a significant positive relationship between the attitude variable and the purchase intention variable. The perceived endorsement variable does not have a significant effect on the attitude variable. There is a significant positive relationship between the perceived quality variable and the attitude variable. The perceived risk variable has no significant positive effect on the attitude variable. The perceived risk variable has no significant positive effect on the purchase intention variable. There is a significant positive relationship between the Subjective Norms variable and the Attitude variable and the Purchase Intention variable.